Atmospheric Rivers Bring More Frequent and Intense Extreme Rainfall Events Over East Asia Under Global Warming. Issue 24 (16th December 2021) - Kamae, Y.; Imada, Y.; Kawase, H.; Mei, W.
Abstract: Portions of East Asia often experienced extremely heavy rainfall events over the last decade. Intense atmospheric rivers (ARs), eddy transports of moisture over the middle latitudes, contributed significantly to these events. Although previous studies pointed out that landfalling ARs will become more frequent under global warming, the extent to which ARs produce extreme rainfall over East Asia in a warmer climate remains unclear. Here we evaluate changes in the frequency and intensity of AR‐related extreme heavy rainfall under global warming using a set of high‐resolution global and regional atmospheric simulations. We find that both the AR‐related water vapor transport and rainfall intensify over the southern and western slopes of mountains over East Asia in a warmer climate. ARs are responsible for a large fraction of the increase in the occurrence of extreme rainfall in boreal spring and summer. ARs will bring unprecedented extreme rainfall over East Asia under global warming. Plain Language Summary: In July 2018 and July 2020, East Asia suffered from extremely heavy rainfall events. The heavy rainfall was observed over a broad area because of organized water vapor flow associated with atmospheric rivers (ARs). ARs received increasing attention over the past decade because of such hazardous events. Under global warming, water vapor transports by ARs are enhanced. Using a set of global and regional atmospheric model simulations, we assessed the great role of ARs in the future extreme rainfall events. ARs with increased water vapor will bring record‐breaking extreme rainfall when they make landfall over China, the Korean Peninsula and Japan. Such a great importance of ARs may also be found over other mid‐latitude regions, including western North America and Europe. Key Points: Atmospheric rivers bring extreme rainfall over East Asia in current and future climates Atmospheric rivers are responsible for a large fraction of the increase in extreme rainfall over East Asia under global warming Intensified water vapor transports by atmospheric rivers cause record‐breaking extreme rainfall events in a warmer climate